The use of marketing communication tools in less developed countries with specific reference to the Eritrean manufacturing industry - Tesfamariam, Tsegazeab Bereketeab (Stellenbosch : Stellenbosch University, 2012)
Thesis (MCom)--Stellenbosch University, 2005.